MANAGEMENT AND ADAPTATION OF HUMAN RESOURCES TO THE CURRENT NEEDS OF SPECIAL STATUS PUBLIC OFFICIALS - Neta-Ionelia ȘAPTEBANI; Marian MOCAN; Alexandra COROIAN; Claudiu ARDELEANU; Cosmina BRATOSIN; Mihai ARDELEAN; Dragoș BORUGĂ (Annals: Series on engineering sciences (Academy of Romanian Scientists))
Human resource management, in the integrated systemic approach of the modern organization, is one of the most important aspects of organizational management since human resources are a vital source of energy for the institution, arguably its most important resource. Effective human resource management can directly lead to increased job satisfaction, positive motivation, loyalty to the institution, significant adherence to the institution's vision and mission, and the establishment of a conducive working climate. All these factors contribute, provided other conditions are met, to the efficiency of the organization in achieving its objectives.